SINGLE DOMAIN ANTIBODIES AND BIOENGINEERING DRUGS ON THEIR BASIS: NEW OPPORTUNITIES FOR DIAGNOSTICS AND THERAPY - E. N. Gorshkova; E. A. Vasilenko; S. V. Tillib; I. V. Astrakhantseva (Медицинская иммунология)
Almost 20 years ago, a unique class of antibodies devoid of L chains was discovered in Camelidae blood serum. Only one variable domain is responsible for antigen recognition in these unusual antibodies. A recombinant protein, which is analogue to such antigen-recognizing variable domain was called the single domain antibody (sdAb), “nanobody” or “nanoantibody”. The single-domain antibodies and their derivatives have been widely used in the field of biology, toxicology and medicine offering new opportunities for diagnosis and treatment of cancer, autoimmune diseases, infectious diseases, and for toxin neutralization. This review focuses on latest researches in the field and concerns some prospectives for creation of nanoantibody-based diagnostic and therapeutic drugs.